Broadband Near-Infrared Photoluminescence and Strong Visible Up-Conversion Emission in BaTiO3-(Na0.5Er0.5)TiO3 Lead-Free Piezoelectric Ceramics. Issue 1 (2nd January 2016) - Li, Jun; Chai, Xiaona; Hui, Xinwei; Wang, Xusheng; Zou, Hua; Zhao, Haifeng; Yao, Xi
Abstract : For checking photoluminescence properties of BaTiO3 -(Na0.5 Er0.5 )TiO3 lead-free piezoelectric ceramics, optical diffuse reflection spectra, visible up-conversion luminescence spectra, 1.55 μm near-infrared photoluminescence spectra, and optical temperature sensing performances under the excitation of 980 nm laser were investigated systematically. Broadband near-infrared (˜1.55 μm, FWHM˜90 nm) emission and strong visible up-conversion (˜550 nm) emission were observed under the 980 nm excitation in the ceramics at room temperature. Near-infrared emission and visible up-conversion emission became stronger with increasing (Na0.5 Er0.5 )TiO3 concentration below quenching point above which it will degrade. The optimal emission intensity was obtained when (Na0.5 Er0.5 )TiO3 content was 7 mol%. These ceramics with excellent ferro-/piezoelectric and photoluminescence properties may be useful for ultrasonic transducer, optical temperature sensor, optical amplifier, and other relative applications.